2016
DOI: 10.5551/jat.35113
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Nanoparticle for Prevention of Atherosclerotic Vascular Diseases

Abstract: Recent technical innovation has enabled chemical modifications of small materials and various kinds of nanoparticles have been created. In clinical settings, nanoparticle-mediated drug delivery systems have been used in the field of cancer care to deliver therapeutic agents specifically to cancer tissues and to enhance the efficacy of drugs by gradually releasing their contents. In addition, nanotechnology has enabled the visualization of various molecular processes by targeting proteinases or inflammation. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 60 publications
0
14
0
1
Order By: Relevance
“…8) The application of PLGA nanoparticles has been studied for the treatment of various diseases, such as bone infection, 9) arteriosclerosis, 10) neurological disorders, 11) cancer, 12) and for use as vaccines. 13) Appropriate infrastructure for a manufacturing process is important for the efficient manufacture of nanomedicines.…”
Section: )mentioning
confidence: 99%
“…8) The application of PLGA nanoparticles has been studied for the treatment of various diseases, such as bone infection, 9) arteriosclerosis, 10) neurological disorders, 11) cancer, 12) and for use as vaccines. 13) Appropriate infrastructure for a manufacturing process is important for the efficient manufacture of nanomedicines.…”
Section: )mentioning
confidence: 99%
“…A pesar de que desde el año 2010 se han sintetizado nanopartículas cargadas con estatinas, estas solo se han utilizado para prevención y tratamiento de arterioesclerosis y tratamiento de hipertensión arterial pulmonar y el cáncer [47][48][49] . El uso de la estatina en tamaño nanométrico, provee control de los eventos adversos en comparación con las dosis sistémicas, gracias a su aplicación selectiva y específica.…”
Section: Sistema De Nanopartículas De Estatinaunclassified
“…The results showed that intravenous treatment with pitavastatin-incorporated nanoparticles did inhibit plaque destabilization and rupture by regulating MCP-1/CCR2-dependent monocyte recruitment in their model. PLGA nanoparticles have also been successfully used for the delivery of pioglitazone, an agonist of peroxisome proliferator-activated receptor-c (PPARc) [67]. In another study, PLGA nanoparticles were loaded with thiazolidinedione (TZD) pioglitazone in hyperlipidaemic mice to determine if the mice could inhibit the activation of macrophages.…”
Section: Atherothrombotic Diseasementioning
confidence: 99%